2018
DOI: 10.1016/s0140-6736(18)30999-1
|View full text |Cite|
|
Sign up to set email alerts
|

Acute rheumatic fever

Abstract: Acute rheumatic fever is caused by an autoimmune response to throat infection with Streptococcus pyogenes. Cardiac involvement during acute rheumatic fever can result in rheumatic heart disease, which can cause heart failure and premature mortality. Poverty and household overcrowding are associated with an increased prevalence of acute rheumatic fever and rheumatic heart disease, both of which remain a public health problem in many low-income countries. Control efforts are hampered by the scarcity of accurate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
195
1
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(208 citation statements)
references
References 125 publications
1
195
1
11
Order By: Relevance
“…We found a lower risk for ARF in those residing in rural areas and found no association with family size. This is contrary to previous studies that reported higher prevalence of ARF among rural residents and among larger families (1,26). The typical explanation was that rural areas and larger families meant crowding and lower socio-economic status (SES) resulting in higher carrier rate of Group A β hemolytic Streptococcus.…”
Section: Multivariable Analysiscontrasting
confidence: 99%
See 2 more Smart Citations
“…We found a lower risk for ARF in those residing in rural areas and found no association with family size. This is contrary to previous studies that reported higher prevalence of ARF among rural residents and among larger families (1,26). The typical explanation was that rural areas and larger families meant crowding and lower socio-economic status (SES) resulting in higher carrier rate of Group A β hemolytic Streptococcus.…”
Section: Multivariable Analysiscontrasting
confidence: 99%
“…Acute rheumatic fever (ARF) is a complication of an autoimmune response to pharyngeal infection with Group A β hemolytic Streptococcus characterized by rheumatologic, cardiac, and neurologic manifestations, and may lead to chronic morbidity and early death (1)(2)(3). ARF is a precursor to rheumatic heart disease (RHD) which may result in irreversible valve damage and heart failure (4,5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Streptococcal M protein binding to type IV collagen in the basement membrane can induce inflammation and fibrosis of valvular cusps [33]. Carbohydrate antigen (Nacetylβ-D-glucosamine) and Group A streptococcus M protein are believed to share the same epitope with human myosin and cardiac valve laminin; this structural similarity may result in antibody-mediated valve structure damage [34]. It was found that there was a large number of peripheral B-cells of active TA patients, and there were CD20+ B cells surrounding the granulomatous lesions [35].…”
Section: Discussionmentioning
confidence: 99%
“…RHD was nearly eliminated in the developed world . With some exceptions, the highest rates of RHD are observed in the developing world . However, indigenous children and those living in remote and socioeconomically deprived communities in Australia and New Zealand have very high rates of ARF and RHD .…”
mentioning
confidence: 99%